Breast and axillary marking in the neoadjuvant setting: survey results from experts of the Brazilian society of mastology - Couto, Henrique Lima; Hassan, Augusto Tufi; Steinmacher, Dalton Ivan; Pessoa, Eduardo Carvalho; Millen, Eduardo Camargo; Zerwes, Felipe; Cavalcante, Francisco Pimentel; Tosello, Giuliano; Novita, Guilherme; Machado Badan, Gustavo; Esteves Francisco, José Luis; Soares, Leonardo Ribeiro; et al. (Frontiers in Oncology, 2024)
Introduction/objectivesThe precise location of the tumor site is essential for the success of surgical treatment. Neoadjuvant chemotherapy (NAC) is a challenge for preoperative tumor and node localization. Thus, the knowledge and attitudes of the affiliated members of the Brazilian Society of Mastology (SBM) regarding breast and axilla marking were evaluated and a consensus regarding management and treatment was reached.MethodsThis was an online survey conducted between June and December 2022. All 1,742 active mastologists affiliated to the SBM were invited anonymously. The online form contained 28 objective questions, of which 22 were formulated on a Likert scale. These questions addressed relevant aspects related to breast and axilla marking in the neoadjuvant setting. Responses that reached 70% agreement were considered consensual. Statistical analysis was performed using the SPSS program version 26.0. Post hoc analysis was performed when appropriate and the significance level was set at p < 0.05. Polychoric regression analyses were conducted using `VGAM` packageResultsIn total, 468 mastologists answered the questionnaire (26.8%), with a predominance of professionals aged between 40–49 years (32.1%). Most professionals were board-certified (84,8%). The indication of tumor marking in the breast prior to NAC was consensual (96.4%) and the metal clip was the preferred method (69.7%). There was no consensus regarding the indication of pre-NAC histologically positive lymph node marking (49.8% disagree and 42.8% agree). However, there was consensus that the clinical and imaging evaluation was insufficient for staging the axilla as N1 (71.6%). The contraindication of breast and node marking in T4b tumors (71.2%) was consensual. There was consensus on the indication of sentinel lymph node biopsy (SLNB) for initially cN1 (92.3%) or cN2 (72.7%) tumors that became cN0 after NAC, with 67.5% opting for dual staining with technetium and patent blue. When <3 lymph nodes were retrieved 41.0% of mastologists performed axillary lymphadenectomy. Among the 28 questions, consensus was reached on only 11 (39.3%).ConclusionThe indication of pre-NAC breast marking is consensual among Brazilian mastologists, although axillary nodal marking is not. There is a great divergence of attitudes among Brazilian surgeons in relation to the many issues related to pre-NAC breast and axilla marking.